ANALISIS KEDUDUKAN HARTA BERSAMA DALAM HUKUM ISLAM DAN KOMPILASI HUKUM ISLAM - Andi Syamsul Bahri (Institut Agama Islam Negeri Bone, 2022)
This study discusses the analysis of the position of joint property in Islamic law and the compilation of Islamic law articles 96 and 97. The purpose of this study is to determine the position of joint property based on the view of Islamic law and compilation of Islamic law articles 96 and 97 as well as the similarities and differences in the position of joint assets according to Islam law and compilation of Islamic law. The author uses a type of library research, which is to become library material as the main data source, by writing, clarifying, and reducing data, especially those related to joint property, both in the study of compilations of Islamic law and Islamic law.The results showed that 1). The position of joint property based on the view of Islamic law can be understood that joint property is syirkah in the sense that it is a form of cooperation or partnership between husband and wife. Syirkah in joint property is a form of cooperation between husband and wife to build a sakinah, mawaddah, warahmah family, including property in marriage. Regarding this joint property, the husband or wife can act to do something or not to do something on the joint property through the agreement of both parties. 2). The position of joint property based on the view of the compilation of Islamic law articles 96 and 97 can be understood that ownership of property in marriage determines the balance between husband and wife in married life. Because they are still married. They have the same rights to the joint property. 3). Equality in the position of joint property according to Islamic law and compilation of Islamic law lies in the distribution of property, in the event of a divorce, the distribution of joint property can be carried out in peace. The division of joint property according to Islamic law and compilation of Islamic law is not absolute because in principle the philosophy in the distribution of joint property is a value that can be achieved by deliberation based on the principles of faith, justice, balance, legal protection, deliberation and compassion. While the difference lies in the concept of joint property. Islamic law does not recognize the name of joint property, Islam views that the wife gets good protection regarding physical, spiritual, moral, material, housing, maintenance costs, and the education of children is the full responsibility of the husband as the head of the family. Meanwhile, according to the compilation of Islamic law, it is explained that joint property is property obtained during marriage as joint property.